Pasting, textural and thermal properties of resistant starch prepared from potato (Solanum tuberosum) starch using pullulanase enzyme - Reddy, Chagam Koteswara (J Food Sci Technol, 2013)
Pullulanase enzyme (40 U/g, 10 h) was used for enzymatic hydrolysis of potato starch which was autoclaved (121 °C/30 min), stored under refrigeration (4 °C/24 h) and lyophilized. Comparison of morphological, pasting, textural and thermal properties among native hydrolysed starch (V2) and gelatinized hydrolysed starch (V3) prepared using pullulanase enzyme on potato starch (V1) were studied. The round, elliptical, irregular and oval shape with smooth surface of V1 was replaced with amorphous mass of cohesive structure leading to loss of granular appearance in V2 and V3. The percentage of amylose and resistant starch content of V2 (27.16 %) and (24.16 %); V3 (51.44 %) and (29.35 %) was higher when compared to V1 (22.17 %) and (3.62 %). The swelling power of V1 observed at 60 °C (0.85 %) and 95 °C (8.64 %) were significantly different from V2 at 60 °C (4.97 %) and 95 °C (7.66 %) and that of V3 at 60 °C (5.82 %) and 95 °C (7.5 %). Significance difference in water solubility (7.62 %) and absorption capacity (6.11 %) was noted in V3 when compared with V1 and V2 owing to amylose/amylopectin content. Increase in water solubility and absorption capacity along with decrease in swelling power of V2 and V3 was noted due to hydrolytic and thermal process. RS obtained from hydrolysis showed a reduction in viscosity, indicating the rupture of starch molecules. The viscosity was found to be inversely proportional to the RS content in the sample. The thermal properties of RS increased due to the retrogradation and recrystallization (P < 0.05).